Lembar kerja siswa matematika berbasis etnomatematika setting historical K.H Ahmad Dahlan di Sekolah Dasar - Ardiana Jayani; Erni Puji Astuti; Wharyanti Ika Purwaningsih; Budi Wibowo (Universitas Muhammadiyah Purworejo, 2020)
The purpose of this study was to produce Student Worksheets (LKS) with K.H. Ahmad Dahlan historical settings for fourth grade students at SD and declared fit for use. The development model used in this research is the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data collection techniques in this study were carried out by documentation, interviews and questionnaires. The instruments used in this study were validation sheets for material experts, media experts, cultural experts and practicality sheets for teachers. The results showed that the developed worksheets the valid criteria with a score of 3.57. The effectiveness criteria cannot be measured because of the Covid 19 virus which causes students to carry out learning online. Practicality criteria are also fulfilled and got a score of 3.93 with good criteria. Based on assessments by material experts, media experts, cultural experts and filling in practicality sheets by the teacher, the products developed are declared valid and practical.